2012
DOI: 10.1371/journal.pone.0040823
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting LTP Requires Neither Repeated Trains for Its Induction Nor Protein Synthesis for Its Development

Abstract: Current thinking about LTP triggered in the area CA1 of hippocampal slices is ruled by two “dogmas”: (1) A single train of high-frequency stimulation is sufficient to trigger short-lasting LTP (1 – 3 h), whereas multiple trains are required to induce long-lasting LTP (L-LTP, more than 4 h). (2) The development of the late phase of L-LTP requires the synthesis of new proteins. In this study, we found that a single high-frequency train could trigger an LTP lasting more than 8 h that was not affected by either an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 78 publications
(98 reference statements)
1
25
2
Order By: Relevance
“…However, in our case, as LTP had been shown to be resistant to the presence of protein synthesis inhibitors (Villers et al 2012), this effect was not present. Conversely, a specific form of potentiation was observed in slices prepared from mutant mice and incubated with rapamycin.…”
Section: Rapamycin Effectcontrasting
confidence: 53%
“…However, in our case, as LTP had been shown to be resistant to the presence of protein synthesis inhibitors (Villers et al 2012), this effect was not present. Conversely, a specific form of potentiation was observed in slices prepared from mutant mice and incubated with rapamycin.…”
Section: Rapamycin Effectcontrasting
confidence: 53%
“…These results and other recent reports (Abbas, 2013;Abbas et al, 2009;Villers et al, 2012) are at odds with many published studies showing that enduring LTP was blocked by protein synthesis inhibitors (Fonseca et al, 2006a;Frey et al, 1988;Osten et al, 1996;Tsokas et al, 2005). Thus, we conducted additional experiments to determine potential sources for the discrepancy.…”
mentioning
confidence: 58%
“…First, our LTP experiments do not support for the protein synthesis hypothesis. We do not stand alone on this matter (Abbas, 2013;Abbas et al, 2009Abbas et al, , 2011Pang et al, 2004;Villers et al, 2012). However, it is important to note that we do not simply report that inhibiting protein synthesis failed to prevent the lasting form of LTP.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…1 h) following induction [8][9][10]. Although rarely cited, there are also a number of very well-controlled studies that have found no effect of protein synthesis inhibition for up to 8 h following the tetanus [11,12]. Finally, the fact that well over a 100 proteins have been claimed to be involved in LTP has led some investigators to lament that understanding this phenomenon will remain forever elusive [13].…”
Section: Multiple Forms Of Long-term Potentiationmentioning
confidence: 99%